2009
DOI: 10.1080/07418820802427833
|View full text |Cite
|
Sign up to set email alerts
|

Career Dimensions of Stalking Victimization and Perpetration

Abstract: Prior literature concerning stalking, particularly in the field of criminology, finds wide variation in fundamental trends regarding stalking victimization and perpetration. There seems to be little consensus regarding when and how stalking is manifested. Furthermore, prior research to date has not addressed the etiology of stalking-related behaviors by applying principles from criminal career research, including participation, frequency, onset, and duration. The present study builds upon prior research by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 36 publications
9
57
0
Order By: Relevance
“…Very little prior research has incorporated a theoretical approach to studying stalking victimization, with the exception of a handful of recent studies that have used college students to examine routine activities theory (Fisher et al, 2002;Mustaine & Tewksbury, 1999), self-control theory (Fox, Gover, & Kaukinen, 2009), life course theory (Nobles et al, 2009), and social learning theory (Fox, Nobles, & Akers, 2011a). Differences in stalking and cyberstalking victimization may portend differences in the nature of offenders, victims, situational antecedents, or all of the above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very little prior research has incorporated a theoretical approach to studying stalking victimization, with the exception of a handful of recent studies that have used college students to examine routine activities theory (Fisher et al, 2002;Mustaine & Tewksbury, 1999), self-control theory (Fox, Gover, & Kaukinen, 2009), life course theory (Nobles et al, 2009), and social learning theory (Fox, Nobles, & Akers, 2011a). Differences in stalking and cyberstalking victimization may portend differences in the nature of offenders, victims, situational antecedents, or all of the above.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study uses a large nationally representative sample of adults in the United States to examine stalking and cyberstalking. With few exceptions (Basile et al, 2006;Black et al, 2011;Fisher et al, 2002;Tjaden & Thoennes, 1998), the majority of stalking research has employed small samples from the general population (Johnson & Kercher, 2009) or college student samples of various sizes (Buhi et al, 2009;Jordan et al, 2007;Mustaine & Tewksbury, 1999;Nobles et al, 2009;Patton, Nobles, & Fox, 2010). While these studies offer valuable information about stalking victimization, their external validity is limited.…”
Section: Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Nationally, substantially more women (8-12%) than men (2-4%) report experiences with stalking (National Violence Against Women Survey (NVAWS), Tjaden and Thoennes 1998). 2 Some research on college students suggests that the majority of stalking victims are women (Bjerregaard 2000;McCreedy and Dennis 1996;Nobles et al 2009) while other research has not found differences in stalking victimization rates for men and women (Cupach and Spitzberg 2000;Haugaard and Seri 2001). Studies involving samples of college students report stalking victimization at much higher rates than the general public.…”
mentioning
confidence: 96%